PULAU BAHANG KOTA (URBAN HEAT ISLAND) DI KOTA YOGYAKARTA DAN DAERAH SEKITARNYA HASIL INTERPRETASI CITRA LANDSAT OLITIRS TAHUN 2013 - Wicahyani, Suksesi; Sasongko, Setia Budi; Izzati, Munifatul (Universitas Negeri Semarang, 2014)
Urban heat island is a phenomenon that urban have higher temperature thansurrounding area. Factors that influence the temperature consist of factors thatcan be controlled by humans, including the city design and structure, totalpopulation , and factors that can not be handled by human, like season, cloudcover, and atmospheric dynamics (Rizwan et al., 2008). The purposes of thestudy were to determine urban heat island in Yogyakarta and its surroundingarea, temperature range, and the role of land cover to the temperature. Urbanheat island type that identified in this study was surface urban heat island. Theheat island was obtained from interpretation of Landsat Imagery catched onSeptember 12, 2013. This image were used to determine the type of land coverbeside temperature. Heat island occurred at Yogyakarta and surrounding area.The heat focused in Yogyakarta City and extended to the north-east of the city.Range the temperature were 5 up to 10Â°C. Land cover associated with the lowtemperature was vegetation while the land cover associated with hightemperature was building area.